GASTROINTESTINAL STROMAL TUMOR - Eiró, Filipa Clara; Borges, Miguel Fróis; Oliveira, Gabriel; Onofre, Susana; Luz, Carlos; Santos, José Carlos; Real, João Corte (Revista Portuguesa de Cirurgia, 2021)
We report a case of an 87-year-old female patient, admitted to our emergency room with an acute abdomen. Exploratory laparotomy revealed a perforated jejunal lesion, histopathological examination was consistent with a gastrointestinal stromal tumor (GIST). GISTs are rare tumors with nonspecific and variable clinical symptoms. An initial clinical presentation as acute abdomen due to perforation, is very rare.